Resíduo seco de cervejaria na alimentação de frangos de corte de crescimento lento - Pires Filho, Israel Costa (2017)
The objective of this study was to evaluate the dry brewery residue (DBR) on production of slow growth poultry. The experiment I, 180 male birds of the Label Rouge line were used, from 14 to 24 days of age to determine the energy values, metabolizable coefficients and the bromatological composition of the DBR. The treatments were distributed in a completely randomized experimental design with five DBR inclusion levels (0, 10, 20, 30 and 40%) and six replicates containing six birds in each experimental unit. The method used was the total collect. After the experimental period, the samples were dried in a forced circulation greenhouse at 55 ° C for analysis of dry matter (DM), crude protein (CP), ethereal extract (EE), gross energy (GE),neutral detergent fiber(NDF), acid detergent fiber (FDA) and the determination of calcium, phosphorus, potassium and magnesium. The bromatological composition for DBR was 91.58% DM, 29.53% CP, 4527 kcal kg -1 GE, 4.96% EE, 65.0% NDF, 25.4% ADF , in the natural matter. The mean values of apparent metabolizable energy (AME), apparent metabolizable energy corrected by nitrogen balance (AMEn), metabolizable coefficient (CMA) and metabolizable coefficient apparent corrected for nitrogen balance (CMAn) for DBR were 2293 kcal kg- 1, 1924 kcal kg-1, 50.65% and 42.50%, respectively, in the natural matter. The mean values of EMA, EMAn, CMA and CMAn for the RSC were 2293 kcal kg-1, 1924 kcal kg-1, 50.65% and 42.50%, respectively. In Experiment II, 980 Label Rouge chicks were used. The treatments were distributed in a completely randomized design, with inclusion levels of DBR (0, 2, 4, 6, 8, 10 and 12%), with seven replicates with 20 birds per experimental unit. Weight and feed intake were recorded at 21, 42 and 63 days for performance evaluation. Blood analysis was performed at 21 and 63 days. At 21 and 63 days, organ yield was obtained and at 63 days the carcass yield, cuts, percentage of fat and meat quality were determined. At 63 days, the dry matter content (DM%) and ammonia bed (NH4) of the were determined. From 1 to 21 days there was a linear effect (P <0.01) for the weight gain(WG). From 1 to 42, there was linear effect (P <0.01) for WG and feed intake (FI), and quadratic effect (P <0.05) for feed conversion (FC). From 1 to 63 days was linear (P <0.01) for WG and FC. At 21 days, serum levels did not suffer (P> 0.05) with DBR. At 63 days glucose and alanine aminotransferase were linear (P <0.05) with CRS and quadratic effect for uric acid (P <0.05). At 21 days the length of the large intestine , the relative weight of the small intestine, the relative weight of the intestine, relative weight of the gizzard (RWG) and relative weight of the pancreas (RWP) had a linear effect (P <0.05). At 63 days the length of the large intestine, relative weight of the large intestine, RWG, RWP, had a linear effect (P <0.05). The yeld of chest WITHOUT BONE and sassame yield was linear (P <0.05) for RSC. There was a quadratic effect for cooking loss (P <0.05). For L* (luminosity - dark and clear), a * (red / green intensity) and b * (yellow / blue intensity) were not influenced (P> 0.05) with DBR. The height vilo and depth of crypt did not have significant effect, as well as the relationship vilo: crypt (P> 0.05),with inclusion DBR levels. The DM% and NH4 values were not significant (P> 0.05). The value of 2% DBR can be indicated for a good performance of slow growing poultry.